Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado